(3GdEHJgGL TQM GdefgGL ddfhhis - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s; (3Gdfhhj,J (B676 (3g` s
(3ChdgG (B:s
(3Chd GdcJGH s
(3BNQgG (B:s
(3CNQcJGH GdLfGFR jJdhg ai GdKGfi cJGH GdRcGI s
(3fSNI SGOSIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs